A Cross-Cultural Study in Spain and Mexico on School Aggression in Adolescence: Examining the Role of Individual, Family, and School Variables. (April 2016) - Estévez, Estefanía; Jiménez, Teresa I.; Cava, María-Jesús
The purpose of the present study was to examine the relationships between family and classroom environments and the development of particular individual characteristics, including level of empathy, attitude to institutional authority, and perceived social reputation, and the role these characteristics may in turn play in aggressive behavior. These factors and associations were analyzed by gender and in two different Latin contexts, Spain and Mexico, from a cross-cultural perspective. Participants in the study were 1, 319 Spanish adolescents and 1, 494 Mexican adolescents drawn from secondary schools. Structural equation models were calculated to test mediational effects among variables. Results obtained indicated, in general terms, that the level of empathy, the social reputation, and the attitude to authority partly mediated the relationship between the environment perceived by boys and girls at home and school, and their aggressive behavior, in both samples. Other similarities and differences between genders and samples were also found and are discussed.